Molecular and clinical analysis of TRPC6 and AGTR1 genes in patients with pulmonary arterial hypertension - Pousada, Guillermo (Orphanet J Rare Dis, 2015)
BACKGROUND: Pulmonary arterial hypertension (PAH) is a rare and progressive vascular disorder characterized by increased pulmonary vascular resistance and right heart failure. The aim of this study was to analyze 5′UTR region in canonical transient receptor potential isoform 6 (TRPC6) and 3′UTR region in Angiotensin II type I receptor (AGTR1) genes in patients with idiopathic and associated PAH. Correlation among mutations and clinical and functional parameters was further analyzed. METHODS: Analysis of TRPC6 and AGTR1 genes was performed by polymerase chain reaction (PCR) and direct sequencing. We used a non-parametric test to determine if significant differences were found between the groups studied and chi-square test to compare clinical and hemodynamic variables among genotypes. RESULTS: Fifty five patients and fifty two controls were included in this study. We found statistically significant differences for c.1-361A > T (p = 0.0077), c.1-254C > G (p < 0.0001) and c.1-218C > T (p = 0.0021) in TRPC6 gene and c.1166A > C (p < 0.001) in AGTR1 gene, between patients and controls. Idiopathic PAH patients (IPAH) and controls presented significant differences for all 3 TRPC6 polymorphisms (p = 0.020), (p = 0.002) and (p = 0.008) respectively, and also showed differences for AGTR1 gene (p < 0.001). In associated PAH (APAH) patients we found statistical differences for c.1-254C > G (p < 0.001) and c.1-218C > T (p = 0.001) in TRPC6 gene and c.1166A > C (p = 0.001) in AGTR1 gene. Several clinical and hemodynamic parameters showed significant differences between carriers and non-carriers of these single nucleotide polymorphisms (SNPs). Nineteen patients were carriers of all 3 SNPs in TRPC6 gene and presented a more severe phenotype with differences in mean pulmonary arterial pressure (p = 0.016), systolic pulmonary arterial pressure (p = 0.040), cardiac index (p < 0.001) and 6 minute walking test (p = 0.049). 16 of these patients harbored the SNP in AGTR1 gene. These patients showed differences in age at diagnosis (p = 0.049), mean pulmonary arterial pressure (p = 0.033), cardiac index (p = 0.002) and 6 minute walking test (p = 0.039). CONCLUSIONS: PAH is a rare disease with pulmonary vascular remodeling caused in part by a heterogeneous constellation of genetic arrangements. This study seems to suggest that c.1-361A > T, c.1-254C > G and c.1-218C > T polymorphisms in TRPC6 gene and c.1166A > C polymorphism in AGTR1 could have a role in the development of this disease.